Effects of high‐dose ethanol intoxication and hangover on cognitive flexibility. (27th October 2016) - Wolff, Nicole; Gussek, Philipp; Stock, Ann‐Kathrin; Beste, Christian
Abstract: The effects of high‐dose ethanol intoxication on cognitive flexibility processes are not well understood, and processes related to hangover after intoxication have remained even more elusive. Similarly, it is unknown in how far the complexity of cognitive flexibility processes is affected by intoxication and hangover effects. We performed a neurophysiological study applying high density electroencephalography (EEG) recording to analyze event‐related potentials (ERPs) and perform source localization in a task switching paradigm which varied the complexity of task switching by means of memory demands. The results show that high‐dose ethanol intoxication only affects task switching (i.e. cognitive flexibility processes) when memory processes are required to control task switching mechanisms, suggesting that even high doses of ethanol compromise cognitive processes when they are highly demanding. The EEG and source localization data show that these effects unfold by modulating response selection processes in the anterior cingulate cortex. Perceptual and attentional selection processes as well as working memory processes were only unspecifically modulated. In all subprocesses examined, there were no differences between the sober and hangover states, thus suggesting a fast recovery of cognitive flexibility after high‐dose ethanol intoxication. We assume that the gamma‐aminobutyric acid (GABAergic) system accounts for the observed effects, while they can hardly be explained by the dopaminergic system. Abstract : High dose ethanol intoxication affects switching in conditions that involve working memory processes, while switching without memory load remains unaffected. These modulations are accompanied by corresponding effects in the anterior cingulate cortex. During states of sober and hangover, no differences were observed, suggesting that the results seem unlikely to be explained via the dopaminergic system but via the gamma aminobutyric acid system.